2021
DOI: 10.1186/s13195-020-00741-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotyping reveals a reduction in the bioavailability of serotonin and kynurenine pathway metabolites in both the urine and serum of individuals living with Alzheimer’s disease

Abstract: Background Both serotonergic signalling disruption and systemic inflammation have been associated with the pathogenesis of Alzheimer’s disease (AD). The common denominator linking the two is the catabolism of the essential amino acid, tryptophan. Metabolism via tryptophan hydroxylase results in serotonin synthesis, whilst metabolism via indoleamine 2,3-dioxygenase (IDO) results in kynurenine and its downstream derivatives. IDO is reported to be activated in times of host systemic inflammation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 57 publications
1
56
2
Order By: Relevance
“…The samples obtained from AD patients showed a deficit of orthologs engaged into the biosynthesis of the amino acids involved in the metabolism of neurotransmitters ( 71 ). These results are in line with other studies which revealed the dysregulation of tryptophan metabolic pathways in AD patients ( 72 , 73 ).…”
Section: Gut Microbiota Composition and Alzheimer's Diseasesupporting
confidence: 93%
“…The samples obtained from AD patients showed a deficit of orthologs engaged into the biosynthesis of the amino acids involved in the metabolism of neurotransmitters ( 71 ). These results are in line with other studies which revealed the dysregulation of tryptophan metabolic pathways in AD patients ( 72 , 73 ).…”
Section: Gut Microbiota Composition and Alzheimer's Diseasesupporting
confidence: 93%
“…The revealed influence of SRO on the HSA–Aβ interaction could be relevant to AD progression, considering the disintegration of the serotonergic system during AD, accompanied by a decrease in the SRO level in biofluids [ 15 , 16 , 39 ]. The SRO concentration in plasma is 0.28–1.7 µM [ 40 ], but in the synaptic cleft it may reach 6 mM and 55 nM after SRO diffuses into the extracellular compartment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin (SRO; 5-hydroxytryptamine, 5-HT) is a HSA ligand closely related to AD pathogenesis (reviewed in [ 15 , 16 ]). It is a phylogenetically conserved monoamine neurotransmitter that performs various physiological functions (behavior regulation, appetite suppression, regulation of energy intake, storage, and expenditure, respiratory drive, hemostasis, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2021) also found that gut microbiota metabolites such as tryptophan metabolites, SCFAs and lithocholic acid are different between AD and controls, which are correlated with altered microbiota and cognitive impairment. In addition, urine and serum serotonin concentrations were found to be significantly lower in patients with AD than in controls (Whiley et al, 2021). Metabolic dysfunction is a basic characteristic of AD.…”
Section: Metabolic Dysfunctionsmentioning
confidence: 90%